Effect of pollutants on biogas steam reforming. (19th January 2017) - Chiodo, V.; Maisano, S.; Zafarana, G.; Urbani, F.
Abstract: This study reports the influence of biogas poisoning on a Ni based catalyst working under steam reforming conditions (atmospheric pressure, T = 1073 K and H2 O/CH4  = 2 mol/mol). A biogas stream composed by CH4 and CO2 with a ratio 55/45 vol.%, added with different chemical species (H2 S, hydrocarbons mixture and D5) as contaminants, was used as inlet gas stream. First, effect of poisoning on Ni catalyst were separately evaluated and the boundary concentrations for each contaminants were revealed (0.4 ppm, 200 ppm and 0.5 ppm for H2 S, hydrocarbons and D5 respectively) to assure Ni stable performances on time on stream (100 h at 50, 000 h −1 of GHSV). Successively, a comparison between Ni catalytic behaviors in presence of two combined poisoning in the biogas (H2 S + Hydrocarbons and Hydrocarbons + D5) was carried out. It was found that the effect of combined poisoning, even though it considered in moderate concentration, is harmful for Ni catalyst activity. Methane conversion on time on stream was reduced from 86% to 40% after 50 h, when the couple of poisoning Hydrocarbons + D5 was added to the inlet gas stream, while a lower deactivation pattern (about 73%) was leaded by couple H2 S + Hydrocarbons. Both poisoning mixtures promoted coke deposition on Ni catalyst surface (about ≥0.5 mgC/gcat ·h) independently by poisoning chemical characteristics probably due to adsorption/deposition of contaminants on catalytic sites. Highlights: The influence of biogas poisoning on a Ni based catalyst working under steam reforming conditions was evaluated. Different chemical species (H2 S, hydrocarbons mixture and D5) were used as contaminants. The combined effect of two poisoning increased the coke formation rates independently by poisoning chemical characteristics.